High-performance and sustainable electrical discharge machining with green microdroplet dielectric - Renpeng Bian; Yonghong Liu; Andong Sun; Xinlei Wu; Peng Liu; Chao Zheng; Yancong Han; Pengxin Zhang; Maoyuan Zhang (Journal of Materials Research and Technology, 2025)
This study presents an electrical discharge machining technique utilizing a low-viscosity, environmentally friendly microdroplet dielectric, aimed at addressing the issues of high surface roughness and environmental pollution associated with conventional kerosene-based dielectrics. To evaluate the impact of the proposed microdroplet dielectric on key machining performance metrics, including material removal rate, machining time, relative electrode wear ratio, and surface roughness, a systematic series of electrical discharge machining experiments was conducted on mold steel. The optimization of the microdroplet content, along with sodium chloride and sodium nitrate concentrations, resulted in enhanced surface quality and integrity of the machined workpieces. The results indicate that the microdroplet dielectric significantly outperformed traditional kerosene, offering enhanced discharge waveform stability. The study found that employing a microdroplet-based dielectric containing 20 % sodium nitrate resulted in a surface roughness of 0.4370 μm, representing a 40.02 % reduction compared to the conventional kerosene-based dielectric. Moreover, the recast layer formed on the surface machined using the microdroplet dielectric was thinner and more uniformly distributed, contributing to improved surface integrity. These findings demonstrate that the proposed dielectric not only improves electrical discharge machining performance but also promotes environmental sustainability, offering promising potential for applications in precision machining and green manufacturing.